Implementation Of Dynamic Governance Concept In Regional Government Of Siak Regency - Mayarni Mayarni (Indonesian Association for Public Administration (IAPA), 2018)
Environmental change encourages the birth of a contextual policy (adaptive policy) that is not only a passive reaction to external pressure but also a proactive approach to innovation, contextualization, and execution. New ideas also result in a contextual policy (adaptive policy) can be executed and generate dynamic governance. Boon and Geraldine formulated Dynamic Governance as